Estrategias metodológicas para potenciar el aprendizaje autónomo en las niñas y niños del séptimo grado en el área de las ciencias naturales de la escuela de educación general básica Adolfo Jurado González,de la parroquia El Sagrario de la ciudad de Loja, periodo lectivo 2014-2015 - Rosales Alberca, Leidy Estafania (2016)
This thesis corresponds to methodological strategies to promote independent learning in children in the seventh grade in the area of natural science school of basic education "Adolfo Jurado Gonzalez" parish El Sagrario, city Loja, academic year 2014-2015, whose overall objective was to propose methodological strategies to improve student learning autonomous seventh grade General school Education Basic "Adolfo Jurado Gonzalez" El Sagrario parish of the city of Loja, period 2014-2015 school; in the pre-experimental methodology and design that facilitated cross-filed; the methods used were scientific, analytical, descriptive, synthetic, inductive and deductive who contributed in the process of analysis and processing of information acquired through the survey technique with the instrument of the questionnaire applied to twenty-eight students and a teacher to elucidate the issues raised by questions about the researched topic; from this aspect it could be concluded that deficiencies autonomous learning diagnosed in students preventing them relate theories to educational practice that impairs proper academic training and the development of methodological strategies contributes to the generation of reflective skills and solvers as base correct acquisition of knowledge, so it is recommended to develop methodological strategies by teachers to contribute to the generation of reflective skills and solvers students as a basis for autonomous learning that contributes to their pedagogical efficiency.